(untitled) (Global Journal of Management and Business Research, 2017)
Forest accounting is creating ground for ecological rationality. World is in danger because of clashes in natural resources particularly ecological ecosystem. There is nexus between forest accounting and sustainable development. Forest is one of the important resources as it is one of the important components of the terrestrial environmental system and larger resource base. Forests provide different basic inputs to the global economic cum ecological system in a multi-dimensional way. It provides timber, fuel wood, pulpwood, fodder, fiber grass and non-wood forest produce